Population decline at distribution margins: Assessing extinction risk in the last glacial relictual but still functional metapopulation of a European butterfly. (16th December 2021) - Sherpa, Stéphanie; Kebaïli, Caroline; Rioux, Delphine; Guéguen, Maya; Renaud, Julien; Després, Laurence
Abstract: Aim: To determine the interplay between climate and land use changes in driving population dynamics in a butterfly species, Coenonympha hero, at the southern limit of its distribution. Location: French Jura massif and Europe. Methods: We analysed patterns of genetic diversity distribution at 817 loci in 136 butterflies from 31 sites using NGS to infer the genetic structure and population size changes over time, using two methods of demographic inference (SNP frequency spectrum analyses and coalescent ABC inferences). We then characterized the climate and land use descriptors of C . hero geographic distribution using species distribution modelling (SDM) and ordination method and compared demographic changes to changes in climatically suitable areas. Results: Coenonympha hero persists in the Jura massif as three core populations that share a common history of decline in two steps: an old decline and a more recent decline that resulted in population fragmentation, the southernmost sites being the most threatened (lowest genetic diversity). Climate change during the Würm glaciation is presumably the main factor explaining the first demographic decline. The second decline started 2000 years ago possibly under increased human pressure as suggested by recent extinctions in several sites nowadays characterized by urban and agricultural surfaces. Both climate and land use variables are important descriptors of C. hero distribution, as SDM predictions were improved by adding aridity index, altitude and land use to bioclimatic predictors. Its habitats include forests in north‐eastern Europe and grasslands in the Jura massif. Main conclusions: Using SDM and genetic demographic inferences, we identified a persistent glacial refuge for the species in Europe. We show that although this relictual population has declined and fragmented under the combined effects of climate warming and anthropization, the metapopulation is still functional but requires particular conservation attention to maintain its connectivity, and to favour the local persistence of this highly endangered butterfly species.